Controlling COVID-19 Pandemic: A Mass Screening Experience in Saudi Arabia - Khan, Anas A.; Alahdal, Hadil M.; Alotaibi, Reem M.; Sonbol, Hana S.; Almaghrabi, Rana H.; Alsofayan, Yousef M.; Althunayyan, Saqer M.; Alsaif, Faisal A.; Almudarra, Sami S.; Alabdulkareem, Khaled I.; Assiri, Abdullah M.; Jokhdar, Hani A. (Frontiers in Public Health, 2021)
A highly accelerating number of people around the world have been infected with novel Coronavirus disease 2019 (COVID-19). Mass screening programs were suggested by the World Health Organization (WHO) as an effective precautionary measure to contain the spread of the virus. On 16 April 2020, a COVID-19 mass screening program was initiated in Saudi Arabia in multiple phases. This study aims to analyze the number of detected COVID-19 cases, their demographic data, and regions most affected in the initial two phases of these mass screening programs. A retrospective cross-sectional study was conducted among the high-risk population as part of the COVID-19 mass screening program across all regions in Saudi Arabia during April and May 2020. A Chi-square test was used to determine the associations between positive cases and various demographic variables. Out of 71,854 screened individuals, 13.50% (n = 9701) were COVID-19 positive, of which 83.27% (n = 59,835) were males. Among positive cases, in the 30–39 years age group, 6.36% were in the active phase, and 2.19% were in the community phase. Based on our experience, launching mass screening programs is crucial for early case detection, isolation, and pattern recognition for immediate public interventions.